Nitrogen use efficiency and recovery in a wheat-corn rotation under tropical savannah conditions - Galindo, Fernando Shintate [UNESP] (2021)
Stable isotopes (e.g., 15N) can be used to develop best practices for fertilizer management in cereal crops under tropical conditions. The objectives of this study were to determine the N contribution from fertilizer and soil to wheat and corn grown in rotation and the residual N contribution from fertilizer applied to wheat and carried over to corn under Brazilian savannah conditions. This study was established in a no-till system on Rhodic Haplustox soil in a randomized complete block design with four replications. The N treatments applied to the wheat crops were 0, 20, 40, 60, 80 and 160 kg (urea-15N) ha−1. The residual effects of N on the succeeding corn crop were evaluated. During the corn phase, two additional treatments were included: a control (0 N) and a treatment with 160 kg N ha−1. Regression analysis showed that the highest estimated wheat yield (5415 kg ha−1) was observed with the application of 114 kg N ha−1. Significant effects from the residual N were observed in the corn shoot biomass and straw N uptake. On average, the recovery rate of the urea N fertilizer was 34% for wheat, and the residual urea N fertilizer use in corn (when applied to wheat) was less than 5% of the amount initially applied. The effect of the residual N was not enough to meet the N demands of the succeeding corn crop. The results of this study provide producers and the scientific community with good estimates of nitrogen use efficiency for wheat and corn.